Analysis productivity of the mine facility department using the objective matrix method (OMAX): case study in coal mining company - Tahir, Ade Putra; Gunawan, Suwardi; Pawitra, Theresia Amelia (Universitas Mercu Buana, 2023)
PT Kideco Jaya Agung is one of the coal mining companies in Paser Regency, East Kalimantan, using an open pit mining system which at the end of 2012 succeeded in realizing the production, transportation, shipping target of 34 million tons. Coal mining is carried out using excavating equipment and hauling equipment. Activities begin with land clearing using bulldozers and / or small excavators, blasting overburden and / or removal of overburden, cleaning coal, loading and transporting coal to the ROM Stockpile. Throughout 2021 there has been a decrease in production results, it is necessary to analyze the productivity of the company's performance, which in this case leads to the Mine Facility department because it is directly related to production. The need to analyze productivity measurements so that it can be seen whether the Mine Facility department in this company is productive or not. The productivity measurement method that can be used to solve the problem is Objective Matrix (OMAX), because the OMAX productivity measurement model overcomes the problems of complexity and difficulty of productivity measurement by combining all important productivity criteria into an integrated form and interrelated with each other and easy to combine.